Should drill or shouldn’t drill? Urban and rural dwellers’ acceptance of geothermal power plant in Mount Slamet protection forest, Indonesia - Qorizki, Dhifa; Permadi, Dwiko B.; Yuwono, Teguh; Rohman, Rohman (Forest and Society, 2021)
Geothermal is one of the new renewable energy, which is more environmentally friendly than the existing fossil energy and has great potential to become an alternative source of energy in the future. However, the level of social acceptance of geothermal power plants operating in forest areas has not been widely studied. This study aims to reveal the social acceptance of affected residents toward the exploration of Baturaden geothermal power plant, operating in the protection forest area of ​​Mount Slamet. The survey was conducted online  to indirectly affected residents living mostly in Banyumas urban areas, while the offline face-to-face survey was administered to the directly affected residents in Sambirata and Karang Tengah villages. A total of 286 samples were analyzed. It was found that the majority of respondents preferred not to continue the establishment of the geothermal power plant, but both rural and urban dwellers have distinctive responses and reasonings. The rural tended to have stronger rejection compared to the urban residents. The acceptance of the project in both groups combined was motivated mainly by the prospect of electricity from more environmentally friendly energy sources and compliance to government policy. Those who refused tend to see from the negative impacts on the disruptions of the daily livelihood in rural areas and environmental damages. Three attitude factors significantly affect the continuation of drilling operation of GPP, namely: economic prospects of geothermal utilization in protection forests, technological optimism to migate the engative impacts, and perceived environmental concerns. To increase the social acceptance, it is suggested that policy makers and energy industry players should integrate the mitigation measures by using more proper technology within the project budget and act harmoniously to increase public awareness of the use of renewable and cleaner energy as well as pay attention to the health, welfare and culture of the local community